Pengaruh Edukasi Sebagai Upaya Pencegahan Penyakit Hipertensi pada Ibu PKK di Asrikaton - Nuril Farid Abshori; Dwi Prasetyo Aji; Kencana Andini; Yustika Kusuma A.S (Jurnal Pengabdian Masyarakat, 2024)
Provision of education related to prevention of hypertension to PKK mothers with the aim of increasing their knowledge regarding the understanding, causes, prevention and treatment of hypertension. So that the information obtained can be conveyed to the family and the closest community. This activity was carried out one day, namely in January 2023 for the PKK Dusun Bunut Kidul, Pakis District, Malang Regency. The material is conveyed through leaflets which contain abbreviations and pictures that represent hypertension. Besides that, a pretest and post test were also given to assess participants' understanding, which was then closed with training on measuring blood pressure and KIE. The results of this study get a significance value of